Performance Enhancement of an Air Cooled Air Conditioner with Evaporative Water Mist Pre-cooling - Najim Abid Jassim, Ass. Prof. Dr. (Journal of Engineering, 2017)
The present paper deals with experimental investigation of the performance of air cooled split air conditioner, with evaporative water mist pre cooling to increase the cooling capacity and reduce the consumption power under hot and dry climate. This investigation considers how the performance can be enhanced by using water mist to pre-cool ambient air entering the condensers by adiabatic cooling process which depends on the ambient air wet bulb temperature; as well the condensing temperature and condensing pressure will be decreased accordingly. So the cooling capacity would be increased and consumption power would be decreased, consequently the energy ratio, EER would be improved. The performance of air cooled air conditioner with water mist pre cooling; ECAC was compared to the performance of air cooled air conditioner, ACAC which tested under the same ambient condition that is ranged from 25 oC to 52 oC. Test results show that ECAC operating at EER of 10.5 BTV/W. The ECAC had an EER of 47 % higher than that of ACAC under the same and most serve hot and dry condition of 52 oC and 10% relative humidity.